Improved Location And Positioning Utilizing Single MIMO Base Station In IMT-Advanced System - Md Isa, Azmi Awang; Othman, Muhammad Hakim; Manap, Zahariah; Mohamad Isa, Mohd Sa'ari; Mohd Zin, Mohd Shahril Izuan; Md Saat, Mohd Shakir; Zakaria, Zahriladha (Penerbit Universiti, UTeM, 2016)
-